(untitled) (Research, Society and Development, 2021)
Objective: to describe an experience of the work of a nursing team in the front line of mass immunization of the population against a COVID-19 by the drive-thru model and the challenges faced. Method: a descriptive study of the experience report type on the performance of the nursing team, over a two-week period, in the immunization against Covid-19 using the drive-thru model in a parking lot in a shopping center in Fortaleza, Ceará, Brazil, in February of 2021. Results: the vaccination site was structured in adequate logistics to meet the quantity of up to 400 vehicles under prior scheduling via the app, with immunization distributed by the previously immunized and trained team. The nursing work process in the handling, maintenance, administration and disposal of immunobiologicals followed the Cold Chain of the National Immunization Program and the challenges faced were related to insufficient inputs, population misinformation and logistics that disfavored other types of transport vehicles. Conclusion: The Nursing team has an important contribution in the operationalization of the National Immunization Campaign against Covid-19, however, it emphasizes the need for a strategy for local management to address the flaws in the logistics of supplying vaccines, strategies to enable access people who do not own a car and fight false news.